Study of Physiochemical Properties of Local Wheat Cultivars and Their Effect on White Layer Cake Quality - Omer, Shano Abdulrahman; Amin Saber, Dlir (Kurdistan Journal of Applied Research, 2019)
Physiochemical and rheological properties of local wheat cultivars were studied to determine and develop their relationship to baking quality of white layer cake. The investigation carried out via studying four different wheat cultivars (Adana, Sham 6, Tamooz 2, and Slemani 2), and comparing to a locally produced flour (from Sulaimani Cereal Milling Company) as control. According to physical parameters, the highest value were obtained by Slemani 2, and in terms of falling number control also recorded the highest. In regards to chemical composition (such as; Protein, Fat, Ash, and Moisture) the greatest values were reported by (Tamooz 2, Sham 6, Adana, and Slemani 2) respectively. Nevertheless, rheological characteristics for farinograph in terms of (water absorption, developing time, stability, and tolerance mixing index), the highest values were achieved by (Tamooz 2, Adana, Control, and Sham 6), respectively. While for amylograph characteristics the highest values were recorded in Slemani 2, and Control in terms of (pasting temperature, and peak viscosity) respectively. The gluten yield parameters tested for gluten index, and dry gluten in which the results obtained for Control, and Sham 6 were the greatest. For physical characteristics of the white layer cake the Control achieved the highest value for volume index, symmetry index, and specific volume. Finally, the Control and Adana have scored the highest values for sensory evaluation. In general, the best white layer cake quality was obtained from the Control, Adana, and Sham 6, hence the protein quality and quantity have great influence on the end product.